Elementary teachers’ pedagogical competencies in supporting students with learning difficulties - Nur Azizah; Mumpuniarti Mumpuniarti; Sari Rudiyati; David Evans (International Journal of Evaluation and Research in Education (IJERE), 2024)
Pedagogical competency is one of four competencies that all teachers need to be proficient within the Indonesian National Teaching Standards. Yet, there is limited understanding of how these competencies relate to inclusive education practice. This study used a combination of survey and interview data to explore the pedagogical skills of elementary teachers working in inclusive schools. Survey data showed that teachers utilized a range of accommodations and modifications within their classrooms to assist them to be inclusive of all students. These accommodations and modifications were often associated with support from other persons (e.g., shadow teacher, parents, peers). While teachers expressed frustration with the learning of students, interview data found that teacher frustration was more about their perceived inability to meet the needs of students. Directions for on-going work to investigate and enhance teacher pedagogical competence within the context of inclusive education Indonesia are discussed.